2021
DOI: 10.1111/1750-3841.15624
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Pu‐erh raw tea from different geographical origins by1H‐NMR and U‐HPLC/Q‐TOF‐MS combined with chemometrics

Abstract: Pu‐erh tea is believed to be a beneficial beverage for health due to its many kinds of pharmacological effects. Nevertheless, detailed information related to differences in metabolites of Pu‐erh raw tea from different geographical origins remains scarce. In this study, 43 elements were found in water‐soluble components of Pu‐erh raw tea by highly sensitive ultra‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry (U‐HPLC/Q‐TOF‐MS). The characteristic groups of 29 metabolites from nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Volatile compounds and metabolites, such as valine, threonine, chlorogenic acid, quinic acid, epiafzelechin, and gallic acid ester, are capable of acting as geographical markers of various teas. These markers have been used to distinguish between black teas from China, India, and Sri Lanka (Yun et al, 2021); Keemun black teas from different regions (Fang et al, 2019); Pu‐erh green tea samples from Zhejiang, Sichuan, Anhui, Henan, Hubei, and Jiangsu provinces (Lv et al, 2015); black tea, green tea, and oolong tea of different origins (Fraser et al, 2012); Pu‐erh teas from different production sites (Wang et al, 2018); Pu‐erh tea from Bada mountain, Jingmai mountain, Nannuo mountain, and Yiwu mountain (Wu et al, 2021); Xinyang Maojian teas of different origins (Wang et al, 2021); and West Lake Longjing tea of different geographical origins (Zhang et al, 2020). Organic acid derivatives, flavonoids, and triterpene glycosides in the leaves and related tea products of Eleutherococcus senticosus can be used for detection of samples adulterated with green tea (Wang, Meng et al, 2019).…”
Section: Mass Spectrometry‐based Metabolomics For Determination Of Ad...mentioning
confidence: 99%
“…Volatile compounds and metabolites, such as valine, threonine, chlorogenic acid, quinic acid, epiafzelechin, and gallic acid ester, are capable of acting as geographical markers of various teas. These markers have been used to distinguish between black teas from China, India, and Sri Lanka (Yun et al, 2021); Keemun black teas from different regions (Fang et al, 2019); Pu‐erh green tea samples from Zhejiang, Sichuan, Anhui, Henan, Hubei, and Jiangsu provinces (Lv et al, 2015); black tea, green tea, and oolong tea of different origins (Fraser et al, 2012); Pu‐erh teas from different production sites (Wang et al, 2018); Pu‐erh tea from Bada mountain, Jingmai mountain, Nannuo mountain, and Yiwu mountain (Wu et al, 2021); Xinyang Maojian teas of different origins (Wang et al, 2021); and West Lake Longjing tea of different geographical origins (Zhang et al, 2020). Organic acid derivatives, flavonoids, and triterpene glycosides in the leaves and related tea products of Eleutherococcus senticosus can be used for detection of samples adulterated with green tea (Wang, Meng et al, 2019).…”
Section: Mass Spectrometry‐based Metabolomics For Determination Of Ad...mentioning
confidence: 99%
“…Nevertheless, to our knowledge, limited research focusing on distinguishing dark teas from distinct altitudes was conducted in the literature. Previous research showed that high-performance liquid chromatography combined with chemometrics was often employed by scholars, implementing limited non-volatile substances in tea such as catechins ( Fang et al, 2019 ), amino acids ( Wu et al, 2021 ), and caffeine ( Su, Wu, Wan, & Ning, 2019 ) as metrics to identify the origin. The process of quantifying and qualifying chemical components to some extent was determined to be complex and costly ( Sun et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pu-erh tea is a traditional and popular type of tea with a long history in Yunnan. According to the processing type and quality characteristics, Pu-erh tea can be divided into raw and ripe forms [2]. In recent years, Pu-erh tea has become increasingly popular with consumers because of its unique health benefits and quality characteristics [3].…”
Section: Introductionmentioning
confidence: 99%